A study of etiology, clinical profile and outcome in children aged 1-12 years presenting with fever of 1-3 weeks duration in a tertiary hospital - Devarajulu, Kavitha; Velusamy, Prabu (International Journal of Contemporary Pediatrics, 2019)
Background: The objective of the study was to find out the etiology, associated signs and symptoms of fever of 1-3 weeks in the age group of 1-12 years and their outcome following treatment in a tertiary care hospital. Methods: This was an observational prospective study conducted at Institute of child health and hospital for children, Egmore, Chennai during the period from January 2011 to October 2012. A total of 621 children aged 1-12 years with 1-3 weeks of fever were included in the study. Demographic, clinical and diagnostic data were collected and analyzed for each patient and outcome was assessed for different types of febrile illness. Results: Out of 621 patients enrolled in the study, enteric fever was diagnosed in majority cases followed by respiratory tract infection, urinary tract infection in 102 (16.4%), leptospirosis in 78 (12.6%), malaria in 60(9.7%), dengue fever in 8 (7.7%) rickettsia infection in 36 (5.8%), tuberculosis in 24 (3.9%), CNS infection in 18 (2.9%), viral hepatitis in12 (1.9%), malignancy in 5(0.8%), connective tissue disorder in 4 (0.6%), localized infection in 2 (0.3%) cases. The incidence was unknown in 10 patients (1.6%). Fever and vomiting were the common symptom seen in all the patients. Mortality was observed 18 (2.94%) cases. Conclusions: The similarity of illness and complexity in etiological conditions demonstrates the complications of diagnosis and treatment of fevers. The present study findings provided rationale information for development of guidelines necessary for treatment and thereby reducing the mortality rate in children of age 1-12 years with incidence of febrile illness.